Lateral Gene Transfer Between Protozoa-Related Giant Viruses of Family Mimiviridae and Chlamydiae. (16th July 2018) - Watanabe, Takanori; Yamazaki, Sumire; Maita, Chinatsu; Matushita, Mizue; Matsuo, Junji; Okubo, Torahiko; Yamaguchi, Hiroyuki
Obligate intracellular chlamydiae diverged into pathogenic and environmental chlamydiae 0.7-1.4 billion years ago. While pathogenic chlamydiae have adapted to a wide range of vertebrates, environmental chlamydiae inhabit unicellular amoebae, the free-living Acanthamoeba . However, how and why this divergence occurred remains unclear. Meanwhile, giant viruses consisting of protozoa-related and protozoa-unrelated viruses have been discovered, with the former group being suggested to have more influenced environmental chlamydiae during their evolution while cohabiting host amoebae. Against this background, we attempted to visualize genes of giant viruses in chlamydial genomes by bioinformatic analysis mainly with comparative genome and phylogenic analysis, seeking genes present in chlamydiae that are specifically shared with protozoa-related giant viruses. As a result, in contrast to protozoa-unrelated giant viruses, the genes of protozoa-related giant viruses were significantly shared in both the chlamydia genomes depending on the giant virus type. In particular, the prevalence of Mimiviridae genes among the protozoa-related giant virus genes in chlamydial genomes was significantly high. Meanwhile, the prevalence of protozoa-related giant virus genes in pathogenic chlamydia genomes was consistently higher than those of environmental chlamydiae; the actual number of sequences similar to giant virus was also significantly predominant compared with those in the environmental chlamydial genomes. Among them, the most prevalent of giant virus was in the case of chlamydiae with Megavirus chiliensis ; total of 1338 genes of the chlamydiae were found to be shared with the virus (444 genes specific to environmental chlamydiae, 892 genes shared between both chlamydiae, only two genes in the pathogenic chlamydiae). Phylogenic analysis with most prevalent sets ( Megavirus chiliensis and Protochlamydia EI2 or Chlamydia trachomatis L2 434Bu) showed the presence of orthologs between these with several clustered. In addition, Pearson's single regression analysis revealed that almost the prevalence of the genes from the giant viruses in chlamydial genomes was negatively and specifically correlated with the number of chlamydial open reading frames (ORFs). Thus, these results indicated the trace of lateral gene transfer between protozoa-related giant viruses of family Mimiviridae and chlamydiae. This is the first demonstration of a putative linkage between chlamydiae and the giant viruses, providing us with a hint to understand chlamydial evolution.